Severe postoperative hyperbilirubinemia in congenital heart disease - Chen Xiaolan (De Gruyter, 2021)
The purpose of our present study was to explore the characteristics and outcomes of congenital heart disease (CHD) patients with severe postoperative hyperbilirubinemia.